Analogues of FAUC 73 revealing new insights into the structural requirements of nonaromatic dopamine D3 receptor agonists - Gmeiner, Peter; Hübner, Harald; et al. (Bioorganic & Medicinal Chemistry, 2004)
Employing the nonaromatic D3 agonist FAUC 73 as a lead compound, the dopaminergic enynes 1a,b and the diene 2 (FAUC 206) were synthesized via palladium-catalyzed cross-coupling. FAUC 206 showed remarkable D3 affinity and enhanced selectivity over D4 when compared to the lead compound. To learn more about the bioactive structure of the diene moiety, computational studies including DFT-based conformational analysis and calculations of the magnetic shielding properties were performed. The electrostatic properties of the pharmacophoric π-systems were visualized by diagnostic MEP maps. © 2003 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.nat.dchph.lphch.analog